Flow study in structure of the plasma torch for microwave plasma spray - Muhammad Fahmi Izuwan, Samion; Nur Ziana, Norizat; Ahmad Redza, Ahmad Mokhtar (Penerbit UMP, 2020)
Microwave oven induced plasma method is a novel application of microwave oven to generate plasma for coating process. It uses 2.45 GHz microwave power and only 0.8 kW input power to produce the plasma which capable of spraying all materials that are considered sprayable. However, the researchesregarding this microwave plasma spray are more to be discovered. Suitable structure of plasma torch is needed for microwave plasma spray that can produce laminar flow to produce desire plasma for coating application. Therefore, this paper will discuss about the suitable structure of plasma torch needed for laminar flow by Reynolds number calculation. Reynolds number calculated by applying the outlet diameter of antenna which is 2, 3 and 4 mm. From this research, Reynolds number from all outer diameter of antenna are below 2000 which indicate laminar flow. The widest plasma diameter achieved at 6.59 mm with 4 mm outlet diameter of antennaand 15 lpm working gas flow rate while the narrowest plasma diameter achieved at 1.26 mm with 3 mm outlet diameter of antenna and 10 lpm flow rates of working gas. The most acceptable condition for producing plasma plume was at 3 mm of antenna diameter with 25 lpm of Ar gas flow rates.